EFICACIA E TOLERABILIDADE DA ASSOCIACAO CAPTOPRIL + HIDROCLOROTIAZIDA NO TRATAMENTO DA HIPERTENSAO ARTERIAL LEVE A MODERADA. ESTUDO MULTICENTRICO - Velasco-Cornejo, I. F. [UNESP]; Cuadrado Martin, L. [UNESP]; Da Silva Franco, R. J. [UNESP] (My University, 1995)
Purpose. To evaluate the antihypertensive efficacy and tolerability of captopril 50 mg + hydrochlorothiazide 25 mg daily in mild to moderate primary hypertension. Methods. Out-patients (n = 471) with mild to moderate hypertension, diastolic blood pressure (DBP) 95-115 mmHg, with 15 days of washout, were included to the treatment initially with half tablet of the association of captopril 50 mg + hydrochlorothiazide 25 mg once daily, for 30 days. After this period, patients with DBP > 90 mmHg had the dosage duplicated, while the others had the same dosage for 60 days more. Evaluation was performed 15 days before and then every month during active drug. Results. Twenty six patients were withdrawn, 13 (2,7%) by adverse effects and 13 by protocol violation. At the end of the wash-out period, the blood pressure (BP), 162 ± 16/103 ± 6 mmHg decreased significantly at the 30th day to 146 ± 14/92 ± 8 mmHg (p < 0,001 vs 0th day); 139 ± 12/86 ± 7 mmHg at the 60th day, (p < 0,001 vs 30th day), and further to 136 ± 11/84 ± 5 mmHg (p < 0,001 vs day 0) till the end of the 90th day. Antihypertensive efficay (DBP ≤ 90 mmHg and decreased for the DBP ≥ 10 mmHg) was obtained in 82% of the patients. There was no difference in BP control considering race, hypertension level, previous antihypertensive treatment and obesity. Cough (4%) was the main adverse event. Conclusion. Captopril + hydrochlorothiazide was effective and safe in the treatment of mild to moderate hypertension. The favorable response was observed in 82% of the patients independently of race, hypertensive level, previous antihypertensive treatment and obesity. Low incidence of side effects was reported, with no difference from others reported in the literature.
Efficacy and tolerability of the association of captopril + hydrochlorothiazide in the treatment of mild-to-moderate hypertension. A multicenter trial
Keywords: angiotensin converting enzyme inhibitor; captopril; hydrochlorothiazide; antihypertensive agent; adult; aged; antihypertensive activity; blood pressure; clinical trial; controlled clinical trial; controlled study; coughing; drug efficacy; drug tolerance; female; human; hypertension; major clinical study; male; oral drug administration; adolescent; drug combination; drug effect; heart rate; hospitalization; middle aged; multicenter study; Adolescent; Adult; Aged; Aged, 80 and over; Antihypertensive Agents; Blood Pressure; Captopril; Drug Therapy, Combination; Female; Heart Rate; Humans; Hydrochlorothiazide; Hypertension; Male; Middle Aged; Severity of Illness Index